2021
DOI: 10.3390/wevj12030095
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Electric Vehicle Cell Innovation Diffusion Considering Patent Licensing Strategy: A Combination of Evolutionary Game and Optimization Algorithm Approach

Abstract: Electric vehicle cell industry is an emerging area with fierce competition on technical innovation, in which the patent holder can choose different innovation diffusion options to maximize the return; however, the strategy is unclear in certain scenarios. We tried to explain the question of how to maximize the patent holder’s return by appropriate patent license strategy to promote EV cell innovation diffusion, when competition and patent licensing relationship exist in the supply chain. A multistage and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The critical decision making for optimal licensing strategies requires further study. Similar to [3], we found that the decision-making space included three major directions: adjusting the patent royalty, increasing the advantage coefficient via investment in R&D, and changing the number of patent pool members.…”
Section: Optimization Algorithmmentioning
confidence: 58%
See 3 more Smart Citations
“…The critical decision making for optimal licensing strategies requires further study. Similar to [3], we found that the decision-making space included three major directions: adjusting the patent royalty, increasing the advantage coefficient via investment in R&D, and changing the number of patent pool members.…”
Section: Optimization Algorithmmentioning
confidence: 58%
“…Sun et al measured China's new energy vehicle patents using a social network analysis approach and suggested that the creation of a patent pool could be a suitable solution to tackle the patent licensing issue in the industry [2]. Sun and Zhang studied a patent licensing strategy to promote the electric vehicle cell innovation diffusion, but the licensor not considering patent pool strategy [3]. Liu et al studied electronic product supply chain patent licensing and outsourcing strategies [4].…”
Section: Literature Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…e evolutionary stability strategy is the final game result of both sides of the game, and it is a longterm steady-state process, while the replicator dynamic equation represents the process of the steady-state approach of the game direction, which is a time function. Because of the limited degree of rationality of human beings, the choices between the game parties are usually variable, and only after repeated choices by both parties can a satisfactory result be obtained [17][18][19].…”
Section: Evolutionary Game and The Construction Of The DL Modelmentioning
confidence: 99%